Modeling the kinetics of potentially toxic elements desorption in sediment affected by a dam breakdown disaster in Doce River - Brazil. (November 2021) - Frachini, Emilli; S Reis Ferreira, Cecilia; Kroetz, Barbara Lunardelli; Urbano, Alexandre; Abrão, Taufik; Santos, Maria Josefa
Abstract: On November 5th, 2015, a mining dam spilled a huge plume of mining waste in the Doce River. Even though many studies have reported the environmental impact from the Doce River's tragedy, the transport of potentially toxic elements (PTE) by kinetic modeling to determine how long the basin takes to achieve the natural balance has not been described. Therefore, samples of sludge, sediment, and water were collected along the Doce River basin, to assess the elements' total leaching by kinetic modeling. The elements Fe, Al, Mn, Cu, Ag, Pb, Cd, and As were evaluated. An innovative mobilization factor (F S / D ) indicated that Mn 2+, Ag +, and Cd 2+ can be mobilized about 80, 89, and 57 times more than its initial concentration. Besides, in low pH, the Al and Pb ions can be mobilized. The desorption kinetics showed a lower rate constant ( k ) and higher initial desorption constant ( h ) for Mn 2+ than Cd 2+ and Ag +, suggesting both high- and low-affinity interaction sites for Mn 2+ . The exponential decay demonstrated that metals can leach for months or years. Thus, the long-lasting release of metals from mining tailing waste in concentrations that endanger the ecosystem and human health makes clear the need for long-term monitoring. Graphical abstract: Image 1 Highlights: A new mobilization factor describes the transport of toxic elements in the basin. Even with specific interactions, Pb, Al, and As ions mobilized in low pH. Kinetics allowed to estimate the half-life in the Mn 2+, Ag +, and Cd 2+ mobilization. Exponential decay indicated long-lasting metal mobilization through the basin. The recovery time of the Doce River can endure months or years.